One-line random input rate and speed service system - Ivnitski, V. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. А. Ивницкий. Однолинейная система со случайной интенсивностью потока и скоростью обслуживанияV. Ivnickis. Vientiesinė sistema su atsitiktiniais įeinančio srauto intensyvumu ir aptarnavimo greičiu